Triple-band metamaterial inspired antenna for future terahertz (THz) applications - Dahlan, ‪Samsul Haimi; Isa Ashyap, Adel Yahya; Kamarudin‬, ‪Muhammad Ramlee; Alamri, S.; A. Majid, Huda; Zainal Abidin, Zuhairiah; Abbasi, Muhammad Inam; Al-Gumaei‬, ‪Yousef Ali; Dahri‬, ‪Muhammad Hashim (Tech Science Press, 2022)
For future healthcare in the terahertz (THz) band, a triple-band microstrip planar antenna integrated with metamaterial (MTM) based on a polyimide substrate is presented. The frequencies of operation are 500, 600, and 880 GHz. The triple-band capability is accomplished by etching metamaterial on the patch without affecting the overall antenna size. Instead of a partial ground plane, a full ground plane is used as a buffer to shield the body from back radiation emitted by the antenna. The overall dimension of the proposed antenna is 484 × 484 μm2. The antenna’s performance is investigated based on different crucial factors, and excellent results are demonstrated. The gain for the frequencies 500, 600, 880 GHz is 6.41, 6.77, 10.1 dB, respectively while the efficiency for the same frequencies is 90%, 95%, 96%, respectively. Further research has been conducted by mounting the presented antenna on a single phantom layer with varying dielectric constants. The results show that the design works equally well with and without the phantom model, in contrast to a partially ground antenna, whose performance is influenced by the presence of the phantom model. As a result, the presented antenna could be helpful for future healthcare applications in the THz band.